Carpal tunnel syndrome: a common initial symptom of systemic wild-type ATTR (ATTRwt) amyloidosis. (2nd January 2016) - Nakagawa, Michitaka; Sekijima, Yoshiki; Yazaki, Masahide; Tojo, Kana; Yoshinaga, Tsuneaki; Doden, Tadashi; Koyama, Jun; Yanagisawa, Shin; Ikeda, Shu-Ichi
Abstract: Background : Systemic wild-type ATTR (ATTRwt) amyloidosis is a prevalent aging-related disorder. However, a limited number of systemic ATTRwt amyloidosis patients have been diagnosed antemortem, and therefore, the prevalence of ATTRwt is underestimated. Here, we investigated clinical findings of a series of systemic ATTRwt amyloidosis patients with antemortem diagnosis. Methods : Thirty-one consecutive patients diagnosed with systemic ATTRwt amyloidosis at Shinshu University Hospital were included in this study. Systemic ATTRwt amyloidosis was diagnosed based on proven ATTR amyloid deposition in biopsy specimens and confirmation of wild-type TTR genotype. Results : The systemic ATTRwt amyloidosis patients consisted of 24 men and seven women, and mean age of onset was 69.8 ± 9.0 years. The most common initial symptom was carpal tunnel syndrome (CTS, 17 patients), followed by heart failure symptoms (14 patients). The mean age at diagnosis was 74.5 ± 8.3 years and the duration of illness from onset to diagnosis was 5.4 ± 4.4 years. Cardiogenic embolism and renal dysfunction are also frequently seen during the course of the disease. Conclusions : CTS is the most common initial symptom of systemic ATTRwt amyloidosis. Our results suggest the possibility of systemic ATTRwt amyloidosis diagnosis at an early stage by carefully examining patients with CTS.